2013
DOI: 10.1227/neu.0000000000000137
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamic Analysis of Intracranial Aneurysmal Bleb Formation

Abstract: Cerebral aneurysm blebs generally form at or adjacent to the point of maximal WSS and are aligned with major flow structures. Wall pressure and OSI do not contribute to determining bleb location. The measurement of WSS using CFD models may potentially predict bleb formation and thus improve the assessment of rupture risk in unruptured aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…Moreover, the flow characteristics just prior to rupture have been reported 44,45 , where both studies demonstrated low WSS on the aneurysm sacs before their rupture. Although the literature on this is scarce, some studies support the notion that WSS decreases sharply in the bleb region after blister formation 8,46 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, the flow characteristics just prior to rupture have been reported 44,45 , where both studies demonstrated low WSS on the aneurysm sacs before their rupture. Although the literature on this is scarce, some studies support the notion that WSS decreases sharply in the bleb region after blister formation 8,46 .…”
Section: Discussionmentioning
confidence: 94%
“…High OSI modulates the gene expression of endothelial cells to upregulate endothelial surface adhesion molecules, cause dysfunction of flow-induced NO, increase endothelial permeability, and thereby promote the rupture process 7,8,47 . In our analysis, six of fifteen reports found a positive correlation between high OSI and IA rupture.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, as concerns the aneurysm rupture risk, height/width ratio and the difference of the dominant A1 artery were correlated with aneurysm rupture. In terms of height/width ratio, these results could be related to more ruptured aneurysms with small impaction zones, higher inflows, and, consequently, a higher wall shear stress (jet inflow) 5)32)39). Aneurysms in the A com complex are more likely to have asymmetric A1 segments and to have asymmetric inflow angiographically from the hypoplastic A1 segment.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of established risk factors for intracranial aneurysm rupture such as family history, female sex, age (the sixth decade), pregnancy, labor, previous aneurysmal subarachnoid hemorrhage, excessive alcohol intake and cigarette smoking (16,21,42,47,48,51,55,26,67,69,(76)(77)(78)81). The morbidity and mortality associated with the surgical and endovascular treatment of unruptured intracranial aneurysm is considerable.…”
Section: Introductionmentioning
confidence: 99%